207k views
1 vote
What is the simplified expression in standard form

What is the simplified expression in standard form-example-1
User Rrvasanth
by
5.5k points

1 Answer

2 votes

Answer:


\boxed{\sf - 2 {p}^(2) - 11p - 35}

Explanation:


\sf \implies - 2 {(p + 4)}^(2) - 3 + 5p \\ \\ \sf \implies - 2( {p}^(2) + 2(p)(4) + {4}^(2) ) - 3 + 5p \\ \\ \sf \implies - 2( {p}^(2) + 8p + 16) - 3 + 5p \\ \\ \sf \implies (( - 2) * {p}^(2) ) + (( - 2) * 8p) + ( ( - 2) * 16) - 3 + 5p \\ \\ \sf \implies (- 2 {p}^(2) ) + ( - 16p ) + (- 32) - 3 + 5p \\ \\ \sf \implies - 2 {p}^(2) - 16p - 32 - 3 + 5p \\ \\ \sf \implies - 2 {p}^(2) + (- 16p + 5p) + ( - 32 - 3) \\ \\ \sf \implies - 2 {p}^(2) - 11p - 35

User Sagish
by
5.7k points